An Investigation into the Level of Iso 9000 Certification and Its Impact on Performance of Ghanaian Firms - Opoku Mensa, R (University of Ghana, 2015)
In the context of globalization and trade liberalization with other European countries in the form of Economic Partnership Agreements, Ghanaian firms should be ready to compete with foreign firms in the global market. ISO 9000 is one of the concepts that have facilitated the institution of sustainable quality management practices across the globe. Meanwhile knowledge and practice of ISO 9000 principles seem to be missing in Africa. The purpose of this study is to find out how the ISO quality management principles affect performance, and to explore the factors that are causing the low patronage of the standards in Ghana. Primary data is collected from ISO 9000 certified and non-certified firms with the use of questionnaire which was analyzed using PLS-SEM technique, some non-parametric tests of comparison and relative importance weight methodology. The results revealed only few significant positive relationships between the individual principles and the five performance indicators. Moreover, quality management principles as a composite variable significantly affect firms‟ performance positively. In comparison, certified firms did perform significantly better in terms of operational performance, product quality and customer satisfaction, but performed insignificantly different from that of non-certified firms in terms of marketing and competitiveness and financial performance. Finally, lack of top management‟s consent seems to be the most considered factor accounting for low patronage of certification, followed by the constraint of resources, financial and human, needed for the implementation process. Most of the non-certified firms, however, indicated their intentions of pursing the ISO 9000 standards in the future.
Keywords: Investigation; Level of ISO 9000; Certification; Impact; Performance